2020
DOI: 10.14336/ad.2019.1120
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Lability at Disease Onset Is an Independent Prognostic Factor of Faster Disease Progression in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fast progressing neurodegenerative disease leading to quadriplegia, anarthria and respiratory insufficiency. A large variety of phenotypes and disability progression requires individually tailored management. Identification of predictors of poor prognosis may not only improve management, but also allow for more precise patients' stratification for clinical trials or research studies. The aim of the study was to investigate the influence of emotional lability present at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Higher HAMA, HAMD, and PSQI score of late‐onset ALS were the likely factor. In addition, one study showed a significant association of emotional lability at onset with faster ALSFRS‐R decline rate 30 . Besides, in late‐onset ALS subgroup, spinal onset or bulbar onset was not found to affect the ALSFRS‐r score and deltaFS, similar as the younger‐onset patients and the entire ALS population 24,25 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Higher HAMA, HAMD, and PSQI score of late‐onset ALS were the likely factor. In addition, one study showed a significant association of emotional lability at onset with faster ALSFRS‐R decline rate 30 . Besides, in late‐onset ALS subgroup, spinal onset or bulbar onset was not found to affect the ALSFRS‐r score and deltaFS, similar as the younger‐onset patients and the entire ALS population 24,25 …”
Section: Discussionmentioning
confidence: 92%
“…As an incurable disease, ALS may exhibit emotional lability and anxiety or depression‐like symptoms at diverse levels 29,30 . Approximately 10% of ALS patients suffered from severe depressive symptoms, 20 which was higher than that of total population with 4%–5% of proportion 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In a German ALS population study, higher education and living in a rural environment was associated with a higher risk of developing ALS [ 148 ]. In addition, emotional ability at disease onset is associated with faster disease progression in ALS [ 149 ]. TAR DNA-binding protein of 43 kDa (TDP-43) is an RNA/DNA-binding protein that regulates mRNA splicing, stability, and translation in the nucleus.…”
Section: Recognition Of Dsdna By Cgas and Formation Of Cgampmentioning
confidence: 99%
“…This condition may arise from the disconnection of brainstem structures from cortical inhibition and can occur in several neurological diseases, such as strokes, traumatic brain injuries, Alzheimer’s disease, multiple sclerosis, amyotrophic lateral sclerosis (ALS), and primary lateral sclerosis (PLS) (Finegan et al, 2019 , 2021 ; Parvizi et al, 2006 , 2009 ; Work et al, 2011 ). At the population level, up to 50% of patients with motor neuron diseases, and in particular those with bulbar upper motor neuron (UMN) involvement, are affected by this condition, and one-third of ALS patients present PBA at diagnosis (Tortelli et al, 2016 ; Hübers et al, 2016 which represents a negative prognostic symptom (Barć et al, 2020 ; Tortelli et al, 2018 ). However, although PBA is a frequent and long-reported symptom, it has remained unclear if this phenomenon is a result of a lack of inhibition from the frontal cortex ("top-down-theory") or due to altered processing of sensory inputs at the brainstem level ("bottom-up-theory") (Bede & Finegan, 2018 ).…”
Section: Introductionmentioning
confidence: 99%